The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/nature05842
|View full text |Cite|
|
Sign up to set email alerts
|

The ATM repair pathway inhibits RNA polymerase I transcription in response to chromosome breaks

Abstract: DNA lesions interfere with DNA and RNA polymerase activity. Cyclobutane pyrimidine dimers and photoproducts generated by ultraviolet irradiation cause stalling of RNA polymerase II, activation of transcription-coupled repair enzymes, and inhibition of RNA synthesis. During the S phase of the cell cycle, collision of replication forks with damaged DNA blocks ongoing DNA replication while also triggering a biochemical signal that suppresses the firing of distant origins of replication. Whether the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
299
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(330 citation statements)
references
References 21 publications
29
299
2
Order By: Relevance
“…Concurrently, also DNA repair factors stored within nucleoli and frequently bound to NCL and NPM1 are released into the nucleoplasm; the transient arrest of the cell-cycle progression possibly facilitates the DNA repair process. Only after resolution of DNA damage, rRNA synthesis is restored, as suggested by the inverse correlation existing between the rDNA transcription rate and c-H2AX foci number (80). Notably, many nucleolar effectors also play a role within the nucleoplasm: beside the contribution to the modulation of the cell-cycle, several reports have pointed out that NCL or NPM1 may directly participate in the DDR.…”
Section: Dynamics Of Dna Repair Proteins During Genotoxic Damage: Nucmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, also DNA repair factors stored within nucleoli and frequently bound to NCL and NPM1 are released into the nucleoplasm; the transient arrest of the cell-cycle progression possibly facilitates the DNA repair process. Only after resolution of DNA damage, rRNA synthesis is restored, as suggested by the inverse correlation existing between the rDNA transcription rate and c-H2AX foci number (80). Notably, many nucleolar effectors also play a role within the nucleoplasm: beside the contribution to the modulation of the cell-cycle, several reports have pointed out that NCL or NPM1 may directly participate in the DDR.…”
Section: Dynamics Of Dna Repair Proteins During Genotoxic Damage: Nucmentioning
confidence: 99%
“…In addition, the nucleolus has been reported to contain several DNA damage sensors (e.g., the ataxia telangiectasia mutated [ATM], the ataxia telangiectasia and Rad3-related [ATR], and p53) (5,123) and it has been demonstrated that, upon DNA damage induction, Pol I-mediated transcription is blocked in an ATM-dependent manner, and not by the DNA damage itself. Interestingly, through microirradiation studies, Kruhlak et al showed that transcription of rDNA is transiently arrested only in damaged nucleoli, whereas the neighboring ones maintain normal transcriptional activity (80). Moreover, Rubbi and Milner, have elegantly shown that nucleolar disruption, rather than DNA damage, may lead to p53 stabilization, suggesting that the nucleolus may constitutively promote p53 degradation, unless DNA damage occurs (124).…”
Section: Dynamics Of Dna Repair Proteins During Genotoxic Damage: Nucmentioning
confidence: 99%
“…14,15,28 DNA damage results in a transient repression of rRNA transcription and a temporary cessation of DNA replication. 25 We found that pretreatment of cells with the specific ATM inhibitor KU55933 could abrogate ADR-inhibited transcription initiation of the rRNA gene (Fig. 6B).…”
Section: Discussionmentioning
confidence: 96%
“…25 To investigate the inhibition of rRNA transcription in ADR-induced DNA damage, we performed northern blot using ITS-1 and ITS-2 as hybridization probes (Fig. 6A).…”
Section: Mutant Of E2f1s31a Abrogates Formation Of Nucleolar E2f1mentioning
confidence: 99%
See 1 more Smart Citation